2017
DOI: 10.3390/rel8120263
|View full text |Cite
|
Sign up to set email alerts
|

The Historical Foundations of Religious Restrictions in Contemporary China

Abstract: Abstract:The ruling Chinese Communist Party (CCP) abolished its total ban on religious activities in 1982. However, the distrust that the CCP feels for religions remains obvious today, and the religious restrictions in contemporary China remain tight. Conventional wisdom tells us that the official atheist ideology of Marxism-Leninism is the main reason behind the CCP's distrust for, and restriction of, religion. However, taking a historical institutionalist perspective, this paper argues that the religious res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“…It is, of course, possible that certain religious activities may be seen by the students and supervisors as too 'overly sensitive' to be chosen as the topics of dissertations, given the suspicions that the Chinese state has on religion (Tao 2017). However, the level of institutional censorship and self-censorship should be not significantly different between dissertations, book chapters, journal articles, monographs, and other academic genres in contemporary China.…”
Section: Methodsmentioning
confidence: 99%
“…It is, of course, possible that certain religious activities may be seen by the students and supervisors as too 'overly sensitive' to be chosen as the topics of dissertations, given the suspicions that the Chinese state has on religion (Tao 2017). However, the level of institutional censorship and self-censorship should be not significantly different between dissertations, book chapters, journal articles, monographs, and other academic genres in contemporary China.…”
Section: Methodsmentioning
confidence: 99%
“…This seems to reflect a higher level of secularisation in the Chinese community, which could be a consequence of the forced process of secularisation undertaken by the Communist party during the 20th century (Tao 2017). While self-identification as non-religious could predate Communist China and the Cultural Revolution (1966)(1967)(1968)(1969)(1970)(1971)(1972)(1973)(1974)(1975)(1976), our data shows that those whose parents were born in China are more likely to declare themselves in this category, and given those people were probably exposed to this religious policy for some amount of time, it is likely to be a significant factor.…”
Section: General Findingsmentioning
confidence: 96%
“…That is to say, the Hakka and Min Nan speakers appear to be significantly more religious than the Mandarin and Wu speakers. This is probably reflective of the turbulent and at times repressive religious policy on the Mainland during the 20th century (Tao 2017).…”
Section: Findings By Subgroup: Languagementioning
confidence: 99%
“…Salehi (1988) demonstrates that the Iranian Revolution of 1978 to 1979 largely benefited from the pre-existing organizations and leadership created by Muslim groups. Tao (2017) shows that only the Communists and Nationalists penetrated religious groups to advance their own agenda for violent uprisings during China's revolutions in the first half of the twentieth century. More directly, by analyzing the experiences of religious leaders and church members in the liberation struggles in Central America in the 1980s, Nepstad (2004) found that religious groups played the most important role in the process of mobilizing collective contention; this was due to the clergy's ability to use 'religious rituals, martyr stories, and biblical teachings to establish a link between faith and activism' among the church members.…”
Section: Trust Social Capital and The Roles Of Religious Groups In mentioning
confidence: 99%
“…Tsai (2007) finds that temples and churches may differ in political status due to particular geo-historical backgrounds: in China, temples usually develop indigenously, and they thus are usually better tolerated by the state and more closely cooperate with the state, whereas churches are believed to have higher subversive potential because of their historical associations with invaders and rebels. Tao (2012Tao ( , 2015 finds that collective contention is less likely to occur in villages with religious groups that simultaneously overlap with civic organizations and local authorities and are hence more likely to 2 For an explanation of the historical foundation of religious restrictions in contemporary China, see Tao (2017); for an update on the religious situation in China, including the country's new regulations on religious affairs that took effect in February 2018, see Albert (2018). serve as credible communication channels between local states and discontented citizens.…”
mentioning
confidence: 99%